154k views
5 votes
Show that the equation represents a circle by rewriting it in standard form, and find the center and radius of the circle.

x^2 + y^2 - 2x + 8y + 1 = 0
standard form
center (x, y) = ( )
radius

User Teunbrand
by
5.0k points

1 Answer

4 votes

Answer:

center is (1,-4)

radius is 4

Explanation:


x^2 + y^2 - 2x + 8y + 1 = 0

standard form is


(x-h)^2+(y-k)^2=r^2, where center is (h,k) and r is the radius

apply completing the square method to get standard form


(x^2 - 2x )+(y^2+ 8y)=-1

take half of the middle term and square it and then add it on both sides


(x^2 - 2x+1 )+(y^2+ 8y+16)=-1+1+16


(x^2-1)^2+(y^2+4)^2=16

center is (1,-4) and r^2 is 16

radius is 4

User Modpy
by
5.2k points